2017
DOI: 10.3171/2015.10.jns151245
|View full text |Cite
|
Sign up to set email alerts
|

Cranioplasty using custom-made hydroxyapatite versus titanium: a randomized clinical trial

Abstract: OBJECTIVE Cranioplasty is routinely performed in neurosurgery. One of its underestimated problems is the high postoperative complication rate of up to 40%. Due to the lack of good prospective studies and the small number of patients (5-20 each year) who receive alloplastic materials, decisions in favor or against a certain material are based on subjective empirical or economic reasons. The main goal of this study-the first prospective, randomized multicenter study in Germany-of custom-made titanium and hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 31 publications
0
43
0
1
Order By: Relevance
“…28 Reddy et al reported that there were no significant differences in the rate of postoperative infection between autologous bone and other materials including HA. 29 Some authors have reported that HA was more beneficial than titanium in terms of the infection rate and the neurological outcome, [29][30][31] and HA block also exhibited good osteoconduction and biocompatibility. [29][30][31][32] In our cases, no case had exposure to or infection of HA even after an 8.7-year follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Reddy et al reported that there were no significant differences in the rate of postoperative infection between autologous bone and other materials including HA. 29 Some authors have reported that HA was more beneficial than titanium in terms of the infection rate and the neurological outcome, [29][30][31] and HA block also exhibited good osteoconduction and biocompatibility. [29][30][31][32] In our cases, no case had exposure to or infection of HA even after an 8.7-year follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…29 Some authors have reported that HA was more beneficial than titanium in terms of the infection rate and the neurological outcome, [29][30][31] and HA block also exhibited good osteoconduction and biocompatibility. [29][30][31][32] In our cases, no case had exposure to or infection of HA even after an 8.7-year follow-up period. Reddy et al reported one-stage reconstruction of soft tissue and skull composite defects using LDMC with vascularized rib grafts.…”
Section: Discussionmentioning
confidence: 99%
“…The reported infection rate ranges from 0% to 32% with up to 75% of patients requiring revision surgery. 18,19,[28][29][30][31] We report our findings of a retrospective analysis comparing hand-molded PMMA implants with CAD/CAM titanium implants for cranioplasty. In our study, the causes for craniectomy then requiring cranioplasty were comparable with available data.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent randomized controlled trial for large defects demonstrated no significant differences between HA and titanium in terms of reoperation and explantation rates which was 11.5% and 12.5%, respectively. [48] …”
Section: Challenges In Cranial Defect Reconstructionmentioning
confidence: 99%